The relationship between management support and individual motivation for knowledge sharing practice - Ali, A.A. (IEEE Computer Society, 2017)
Knowledge sharing is a key process that influences individual and organizational performance. The significance of sharing knowledge is confirmed through enormous number of previous studies. However individuals are not always motivated to share their knowledge. There are different factors might encourage or hinder employees to engage in knowledge sharing. This study aims at investigating the impact of the management support of an organization on the individual motivation for knowledge sharing. The proposed model reflects the structure of the constructs under investigation. The study uses a sample of 157 respondents collected from the oil and gas sector. The data were collected through survey method using an online questionnaire. The measurements were analyzed using the reliability analysis to confirm their internal consistency. Furthermore, the correlation matrix was generated to check on the significance of the interrelationship and to ensure the nonexistence of collinearity issue among the model constructs. The study applies the Structural Equation Modeling (SEM) techniques to validate the model and test the proposed hypotheses. The findings show that there is a strong positive relationship between management support and individual motivation for knowledge sharing. Therefore, the organizational support from top and middle management motivate employees to share their knowledge and experience with each other. © 2017 IEEE.